2017
DOI: 10.1037/edu0000197
|View full text |Cite
|
Sign up to set email alerts
|

Four semesters investigating frequency of testing, the testing effect, and transfer of training.

Abstract: We carried out 4 semester-long studies of student performance in a college research methods course (total N ϭ 588). Two sections of it were taught each semester with systematic and controlled differences between them. Key manipulations were repeated (with some variation) across the 4 terms, allowing assessment of replicability of effects. Variables studied included frequency of tests (e.g., 2 vs. 8 in-class exams), the repetition of some and not other exam items (i.e., the testing effect), and variation of tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 42 publications
1
16
0
Order By: Relevance
“…Although the lack of overlap information should be rectified in future work, there is evidence that retrieval practice can make a difference even when the test questions are not the same as the quiz questions (i.e., when they are new, related questions from the textbook, Batsell, Perry, Hanley, & Hostetter, ). In fact, Foss and Pirozzolo () did not observe consistent superiority for items that were repeated exactly over those that were repeated in modified form; the reverse was more often the case.…”
Section: Discussionmentioning
confidence: 93%
“…Although the lack of overlap information should be rectified in future work, there is evidence that retrieval practice can make a difference even when the test questions are not the same as the quiz questions (i.e., when they are new, related questions from the textbook, Batsell, Perry, Hanley, & Hostetter, ). In fact, Foss and Pirozzolo () did not observe consistent superiority for items that were repeated exactly over those that were repeated in modified form; the reverse was more often the case.…”
Section: Discussionmentioning
confidence: 93%
“…A meta-analysis by Bangert-Drowns, Kulik, and Kulik (1991) found large learning gains for testing over no testing, but that increasing the frequency of assessment beyond three assessments resulted in smaller learning gains. More recently, Foss and Pirozzolo (2017), found that across four semesters students assessed more frequently scored higher on a final exam with a small effect size (d = 0.16). However, the difference between the conditions was only significant for one of the semesters.…”
Section: Frequency Of Assessmentsmentioning
confidence: 99%
“…Other studies are limited because they lack a restudy control condition but compare the testing condition to conditions in which no exposure to information subsequent to the initial learning took place (McDaniel et al, 2007a, 2011, 2013; Johnson and Kiviniemi, 2009; Mayer et al, 2009; Vojdanoska et al, 2010; Lyle and Crawford, 2011; Roediger et al, 2011; Marsh et al, 2012; Shapiro and Gordon, 2012; Bell et al, 2015; Downs, 2015; Khanna, 2015; Batsell et al, 2017; Foss and Pirozzolo, 2017). In these studies, the testing effect is confounded with differences in exposure to and engagement with learning content, which severely limits the interpretation of their findings.…”
Section: Introductionmentioning
confidence: 99%